Transgressive women don't deserve protection: young men's narratives of sexual violence against women in rural Papua New Guinea. Issue 11 (1st November 2016) - Kelly-Hanku, A.; Aeno, H.; Wilson, L.; Eves, R.; Mek, A.; Nake Trumb, R.; Whittaker, M.; Fitzgerald, L.; Kaldor, J. M.; Vallely, A.
Abstract: Sexual violence against women and girls is commonplace in Papua New Guinea (PNG). While the experiences of women are rightly given central place in institutional responses to sexual violence, the men who perpetrate violence are often overlooked, an oversight that undermines the effectiveness of prevention efforts. This paper draws on interviews conducted with young men as part of a qualitative longitudinal study of masculinity and male sexuality in a rural highland area of PNG. It explores one aspect of male sexuality: men's narratives of sexual violence. Most striking from the data is that the collective enactment of sexual violence against women and girls is reported as an everyday and accepted practice amongst young men. However, not all women and girls were described as equally at risk, with those who transgress gender roles and roles inscribed and reinforced by patriarchal structures, at greater risk. To address this situation, efforts to reduce sexual violence against women and girls require an increased focus on male-centred intervention to critically engage with the forms of patriarchal authority that give license to sexual violence. Understanding the perceptions and experiences of men as perpetrators of sexual violence is a critical first step in the process of changing normative perceptions of gender, a task crucial to reducing sexual violence in countries such as PNG.